2017
DOI: 10.1186/s12917-017-1091-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stochastic agent-based model to evaluate surveillance strategies for detection of emergent porcine reproductive and respiratory syndrome strains

Abstract: BackgroundThe objective of the current study was to develop a stochastic agent-based model using empirical data from Ontario (Canada) swine sites in order to evaluate different surveillance strategies for detection of emerging porcine reproductive and respiratory syndrome virus (PRRSV) strains at the regional level. Four strategies were evaluated, including (i) random sampling of fixed numbers of swine sites monthly; (ii) risk-based sampling of fixed numbers, specifically of breeding sites (high-consequence si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Prior studies suggested that the practice of equipment sharing was associated with the spread of infectious diseases, which was consistent with our findings (39,40). The high indirect contact rates between large and small farms in Uganda could be partly because large farm owners can afford farm equipment as opposed to the surrounding small farm owners who frequently borrow the equipment (11,17).…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies suggested that the practice of equipment sharing was associated with the spread of infectious diseases, which was consistent with our findings (39,40). The high indirect contact rates between large and small farms in Uganda could be partly because large farm owners can afford farm equipment as opposed to the surrounding small farm owners who frequently borrow the equipment (11,17).…”
Section: Discussionsupporting
confidence: 89%
“…This is the first evaluation of a human leptospirosis surveillance system that we are aware of, and therefore there is not much to compare it to. However, scenario tree modeling has been frequently used to assess and improve surveillance systems for different illnesses, with most of these assessments concentrating on animal productivity and health ( 26 , 42 44 ).…”
Section: Discussionmentioning
confidence: 99%